Understanding mAb aggregation during low pH viral inactivation and subsequent neutralization. Issue 3 (11th December 2019) - Wälchli, Ruben; Ressurreição, Mariana; Vogg, Sebastian; Feidl, Fabian; Angelo, James; Xu, Xuankuo; Ghose, Sanchayita; Jian Li, Zheng; Le Saoût, Xavier; Souquet, Jonathan; Broly, Hervé; Morbidelli, Massimo
Abstract: Monoclonal antibodies (mAbs) and related recombinant proteins continue to gain importance in the treatment of a great variety of diseases. Despite significant advances, their manufacturing can still present challenges owing to their molecular complexity and stringent regulations with respect to product purity, stability, safety, and so forth. In this context, protein aggregates are of particular concern due to their immunogenic potential. During manufacturing, mAbs routinely undergo acidic treatment to inactivate viral contamination, which can lead to their aggregation and thereby to product loss. To better understand the underlying mechanism so as to propose strategies to mitigate the issue, we systematically investigated the denaturation and aggregation of two mAbs at low pH as well as after neutralization. We observed that at low pH and low ionic strength, mAb surface hydrophobicity increased whereas molecular size remained constant. After neutralization of acidic mAb solutions, the fraction of monomeric mAb started to decrease accompanied by an increase on average mAb size. This indicates that electrostatic repulsion prevents denatured mAb molecules from aggregation under acidic pH and low ionic strength, whereas neutralization reduces this repulsion and coagulation initiates. Limiting denaturation at low pH by d ‐sorbitol addition or temperature reduction effectively improved monomer recovery after neutralization. Our findings might be used to develop innovative viral inactivation procedures during mAb manufacturing that result in higher product yields. Abstract : Aggregate formation during the viral inactivation (VI) step can reduce the yield of mAb downstream processing. Wälchli and coworkers analyzed the aggregation behavior of two mAbs under VI conditions and observed that the molecules denature at low pH but only aggregate after neutralization. Reducing denaturation under acidic conditions through additives or by decreasing temperature substantially improves monomer yield for this processing step.